2011
DOI: 10.1073/pnas.1102261108
|View full text |Cite
|
Sign up to set email alerts
|

Linkage maps from multiple genetic crosses and loci linked to growth-related virulent phenotype in Plasmodium yoelii

Abstract: Plasmodium yoelii is an excellent model for studying malaria pathogenesis that is often intractable to investigate using human parasites; however, genetic studies of the parasite have been hindered by lack of genome-wide linkage resources. Here, we performed 14 genetic crosses between three pairs of P. yoelii clones/subspecies, isolated 75 independent recombinant progeny from the crosses, and constructed a high-resolution linkage map for this parasite. Microsatellite genotypes from the progeny formed 14 linkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(104 citation statements)
references
References 43 publications
5
98
0
1
Order By: Relevance
“…We demonstrated that different innate pathways were stimulated when inbred mice were infected with the two isogenic parasite strains. In our previous study, we showed that out of 21 microsatellites, only one (Py2000 on chromosome 8) was polymorphic between the genomes of N67 and N67C parasites, and sequencing of the gene encoding PyEBL found only one nucleotide substitution leading to an amino acid change at position 741 (C to Y) (34). These results demonstrate that dramatic differences in disease phenotypes can be produced when mice are infected with different parasite strains, even with parasites of similar genomic backgrounds.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We demonstrated that different innate pathways were stimulated when inbred mice were infected with the two isogenic parasite strains. In our previous study, we showed that out of 21 microsatellites, only one (Py2000 on chromosome 8) was polymorphic between the genomes of N67 and N67C parasites, and sequencing of the gene encoding PyEBL found only one nucleotide substitution leading to an amino acid change at position 741 (C to Y) (34). These results demonstrate that dramatic differences in disease phenotypes can be produced when mice are infected with different parasite strains, even with parasites of similar genomic backgrounds.…”
Section: Discussionmentioning
confidence: 85%
“…The parasite P. yoelii nigeriensis N67 (N67) and N67C were initially obtained from the Malaria Research and Reference Reagent Resource Center (MR4; www.mr4.org/) and was described previously (34). Freshly thawed parasites were injected into naïve C57BL/6 mice to initiate infection.…”
Section: Methodsmentioning
confidence: 99%
“…For these and the remaining studies, mice were infected with P. yoelii nigeriensis (N67) (17) or with P. yoelii yoelii 17XNL (kindly provided by A. Rodriguez). Although these closely related subspecies differ in growth rate (N67's growth is fast; 17XNL's is slow) and lethality (N67 is lethal; 17XNL is nonlethal), infections with these subspecies yield peak parasitemias in inbred (C57BL/6) and outbred (CD-1, Kunming) mice by 11 days postinfection (49) and in CBA/J mice by 10 days postinfection. Neither parasite was lethal in CBA/J mice.…”
Section: Resultsmentioning
confidence: 99%
“…Mice were challenged with homologous P. yoelii 17XNL strains unless otherwise described, in which case they were challenged with P. yoelii P265BY, which is genetically different from P. yoelii 17XNL [25], or with P. berghei ANKA [26].…”
Section: Tmp-smx Formulation and Dosementioning
confidence: 99%